Preliminary results of using the holographic facility to study the ecology of coastal plankton in Lake Baikal - Naumova, Elena Yu (Proceedings of SPIE)
The establishment of stationary monitoring stations is a timely and topical issue. The coastal zone of Lake Baikal is particularly affected by global climate processes and human activities. During the observations carried out in August 2021 in the coastal zone of Lake Baikal, it was reliably established that the miniDHC (Digital Holographic Camera) can be used to monitor qualitative and quantitative changes in coastal plankton. Lake Baikal is a good test site for improving the technique of monitoring changes in the world ocean. Despite their diversity, freshwater plankton can be better identified than marine plankton. The miniDHC holographic camera, if used over a long period of time, will provide new data on the ecology of the coastal area. The combination of new and traditional methods in the study of the coastal zone of Lake Baikal is necessary and extremely effective